Financial Technology: Blockchain - Down to Earth - Markus Demary; Vera Demary (Institut der deutschen Wirtschaft (IW), 2017)
The blockchain technology offers the promise to be cheaper, faster, less error-prone and safer compared to traditional financial services. Whether a market for blockchain services will emerge, depends, however, on several criteria.
Keywords: 330